Application of the Ijarah Agreement in Al-Badar Syariah Hotel Room Rental in Makassar - Risna Aulia; Muryani Arsal; Muhammad Khaedar Sahib (International Journal of Economic Research and Financial Accounting, 2024)
The aim of this research is a qualitative type of research with the aim of knowing the application and implementation of the ijarah (rental) contract at Al-Badar Hotel Syariah Makassar. The Ijarah contract is a rental contract entered into by both parties to the agreement between the mu'ajir (the person who rents) and the musta'jir (the person who rents) both parties benefit from the replacement of the rent. And also this research aims to determine the compatibility of the ijarah (lease) agreement with the DSN-MUI Fatwa regarding Ijarah. The method used in collecting data was obtained from interviews and documentation. The data sources used are primary data and secondary data. This type of research includes field research. The results of the research obtained are that the implementation of the ijarah contract for renting rooms at the Al-Badar Syariah Makassar hotel is carried out based on an agreement between both parties, namely between the hotel (receptionist) and the room renter by paying the rent to the hotel according to the price agreed upon by both parties. both parties. And the suitability of the ijarah agreement for renting Al-Badar Syariah Makassar hotel rooms is in accordance with the DSN-MUI Fatwa regarding ijarah with the fulfillment of the pillars and conditions of ijarah.